Analisis Dampak Penerapan Good Corporate Governance (GCG) terhadap Kinerja Perusahaan Bank Syariah (Studi Kasus: PT. Bank Tabungan Negara (Persero) Tbk, KCP Syariah Solok) - Sintia Maulida; Era Sonita (ARZUSIN, 2026)
Good Corporate Governance (GCG) has become an important issue in corporate governance studies, particularly in the Islamic banking industry, but studies that specifically discuss the implementation of GCG and its impact on corporate performance at the branch office level remain relatively limited. This study aims to analyze the implementation of GCG and its impact on corporate performance at PT. Bank Tabungan Negara (Persero) Tbk, KCP Syariah Solok. This study used a qualitative approach with a case study design. The research participants consisted of leaders and employees directly involved in the implementation of GCG within the company, selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The results show that PT. Bank Tabungan Negara (Persero) Tbk, KCP Syariah Solok has implemented the principles of GCG, namely transparency, accountability, responsibility, independence, and fairness in the company’s operational activities. This implementation is reflected in information disclosure to customers, a clear division of duties and responsibilities, compliance with standard operating procedures and Islamic banking regulations, objective decision-making, and the provision of fair services to customers. The implementation of GCG also has a positive impact on corporate performance, particularly in improving work effectiveness, service quality, operational compliance, strengthening the internal control system, and public trust. The conclusion of this study affirms that GCG is an important factor in supporting improved corporate performance and organizational sustainability. The implications of this study provide theoretical contributions to the development of GCG studies, agency theory, and stakeholder theory in the context of Islamic banking, as well as practical implications for banking management in strengthening human resource competence, internal control systems, and operational supervision.